A new design of regenerative flow turbine with improved performance for residential applications - Alperen Bugra Colak; Oğuz Arslan (Case Studies in Thermal Engineering)
Regenerative flow turbines (RFTs) are increasingly used for power generation in small-scale applications such as residential use. Although they are adequate for the use of waste energy, the efficiency of RFTs still needs to be improved. This study investigates the performance improvement of the conventional RFT (α = 0°) by optimizing the blade geometry to obtain the maximal momentum transfer. Computational fluid dynamics (CFD) analyses were conducted for low temperatures of 363 K and 393K and high temperatures of 475 and 500K, as available for residential use. The performance of the designs and formed ORC was evaluated through energy and exergy analyses. As a result, it was determined that it is possible to increase the maximum power generation from 0.81 kW to 0.89 kW by an increase rate of 9.42 % for high-temperature scales, while it is possible to increase the maximum power generation from 0.21 kW to 0.23 kW by an increase rate of 9.71 % for low-temperature scales. It was determined that it is possible to increase energy efficiency from 11.26 % to 14.72 % by a rate of 30.73 % and exergy efficiency from 10.77 % to 12.54 % by 16.49 % for low-temperature applications. Also, it is available to increase energy efficiency from 12.16 % to 14.67 % by an increase rate of 20.64 %, and exergy efficiency from 6.80 % to 7.99 % by an increase rate of 17.45 % for high-temperature applications. These results record an exergy efficiency increase of up to 0.205 pp at 1500 rpm and up to 0.420 pp at 3000 rpm for a low-temperature ORC system. For the high-temperature applications (475–500K), an increase in the exergy efficiency up to 0.129 pp is available.